Belajar Strategi Pengembangan SQ Kepada Muhammad SAW - Abdul Wahid Hasan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
The Spiritual Intelligence (SI) or Spiritual Quotient (SO) discourse has become an interesting study in the realm of education and psychology since Danah Zohar and Ian Marshall introduced SQ theory as the third intelligence, the ultimate intelligence and the necessary foundation for the effective functioning of both IQ and EO. Ironically, the researchers of SO coming from west who are non-Moslems have never mentioned Muhammad, as a man having high SO. Whereas in fact, his great, nobility and spirituality have been recognized by intelligentsia from both Moslems and non-Moslems. In other hand, he is the greatest educator to the humankind. This paper tries to place Muhammad figure (pbuh) more objectively and wisely in the SQ discourse, and at the same time it explains how he teachs and educates his students so they become the renowned-world individuals leading the world and having high intelligence not only IQ and EQ but also SQ like AbuBakar, Umar, Ali etc.